Medical ethics today : the BMA's handbook of ethics and law (Wiley-Blackwell, 2012)
This is your source for authoritative and comprehensive guidance from the British Medical Association (BMA) Medical Ethics Department covering both routine and highly contentious medico-legal issues faced by health care professionals